al-Lughah al-‘Arabīyah ka-Lughah ‘Ālamīyah wa-al-Tanabbu’ ‘an Mustaqbalihā fī al-Mujtama‘ al-Nījīrī - Idris Ahmad Yunus; Saleh Muhammad Kabir (Al-Ma‘rifah, 2021)
Since the 20th century AD, Arabic has become a global language used at the United Nations in speaking, making official speeches, issuing documents, and in simultaneous translation into official languages, in addition to being an official language in the Organization of African Unity and other international organizations of the United Nations Africa remained related to Arab trade and civilization centuries before Islam, and when Islam came, the first Arab migration to the African continent was the migration to Abyssinia, and thus the Muslim Arabs found their first home after their homeland in Africa. Islam entered Kanem Borno in the 8th century, and in Kano in the 14th century. As for the western region; the country of Yoruba, reached it in the first half of the 14th century AD according to one saying and the 15th according to another, and the 16th according to a third. As for the eastern region, whose population is mostly Igbo, it was reached by displaced merchants from the two regions: the northern and western. The masters of the Arabic language in Nigeria have made effective efforts to advance the Arabic language, as these efforts herald the splendid independence of the Arabic language in Nigerian society.